An examination of an adapted Project ECHO model series during the COVID‐19 pandemic in Idaho - Jonathan D. Moore; Julio deLeon Gonzalez; Madeline P. Casanova; Kathleen Rodgers; Russell T. Baker (Wiley, 2023)
Abstract Introduction Idaho is a medically underserved and rural state comprised mostly health professional shortage areas for primary and specialty care. Given the state shortages and barriers to access care, the testing and treatment of COVID‐19 may be improved through the implementation of telementoring education programs such as Project Extension for Community Healthcare Outcomes (ECHO). The purpose of this article was to assess session attendance and self‐reported healthcare clinician perceptions of the ECHO Idaho COVID‐19 series (2020 and 2021), a modified Project ECHO model provided during the COVID‐19 pandemic in Idaho. Methods ECHO Idaho developed a COVID‐19 ECHO series for healthcare providers to attend in 2020 and 2021. The sessions included COVID‐19 updates specific to Idaho, didactic presentations on prevention, screening, diagnosis, and evidence‐based treatments for COVID‐19, and case‐based presentations. Results A total of 664 individuals attended the 2020 series and 260 individuals attended the 2021 series, with 1752.5 continuing medical education hours being claimed. Participants reported series participation increased overall knowledge of COVID‐19, knowledge of best practices for treatment, and awareness of resources available in Idaho. Further, series participation was perceived to reduce feelings of isolation, enhance access to information, and support healthcare professionals (e.g., provided resources) during the pandemic. Conclusion Results of this evaluation indicate that the ECHO Idaho COVID‐19 series was a useful and valuable program to implement during a pandemic in a rural and frontier state to improve physician knowledge and specialty training.